Complex chemoattractive and chemorepellent Kit signals revealed by direct imaging of murine mast cells in microfluidic gradient chambers() - Shamloo, Amir (2013)
Besides its cooperating effects on stem cell proliferation and survival, Kit ligand (KL) is a potent chemotactic protein. While transwell assays permit studies of the frequency of migrating cells, the lack of direct visualization precludes dynamic chemotaxis studies. In response, we utilize microfluidic chambers that enable direct observation of murine bone marrow-derived mast cells (BMMC) within stable KL gradients. Using this system, individual Kit+ BMMC were quantitatively analyzed for migration speed and directionality during KL-induced chemotaxis. Our results indicated a minimum activating threshold of ~3 ng ml(−1) for chemoattraction. Analysis of cells at KL concentrations below 3 ng ml(−1) revealed a paradoxical chemorepulsion, which has not been described previously. Unlike chemoattraction, which occurred continuously after an initial time lag, chemorepulsion occurred only during the first 90 minutes of observation. Both chemoattraction and chemorepulsion required the action of G-protein coupled receptors (GPCR), as treatment with pertussis toxin abrogated directed migration. These results differ from previous studies of GPCR-mediated chemotaxis, where chemorepulsion occurred at high ligand concentrations. These data indicate that Kit-mediated chemotaxis is more complex than previously understood, with the involvement of GPCRs in addition to the Kit receptor tyrosine kinase and the presence of both chemoattractive and chemorepellent phases.